A cross-sectional study on prevalence of menstrual problems, lifestyle, mental health, and PCOS awareness among rural and urban population of Punjab, India. (3rd July 2022) - Sharma, Priya; Kaur, Mandeep; Kumar, Sachin; Khetarpal, Preeti
Abstract: Introduction: Menstrual cycle gets affected by various modifiable risk factors. To assess prevalence of various types of menstrual problems, lifestyle and mental health status, identification of variables as predictors for menstrual problems and level of polycystic ovary syndrome (PCOS) awareness among rural and urban population of Punjab, the present study has been carried out. Methods: The study was conducted from November 2019 to July 2020 in the Malwa region of Punjab, India, with 2673 participants (15–25 years). Epidemiological information was collected using predesigned questionnaire along with depression, anxiety and stress (DASS-21) score mental health assessment tool. MS-Excel (2019) and IBM SPSS 18.0 (SPSS Inc., Chicago, IL) was used for statistical analysis. Results: The overall prevalence of different menstrual problems was 60.61%, with dysmenorrhea (50.64%) being most common problem. Body mass index (BMI), menarche age, physical activity, and mental health status are significant ( p < 0.05) predictors of menstrual problem both in rural and urban population. Overall, only 3.30% subjects were aware about PCOS. Conclusion: Dysmenorrhea is the most common menstrual problem, both in rural and urban population. BMI, sedentary lifestyle, electronic gadgets usage, and mental health are associated with menstrual problems. Low awareness on PCOS indicates need to create awareness as the condition can be easily managed with early intervention.